A new species of Parotocinclus (Loricariidae: Hypoptopomatinae) from Rio Tocantins basin, Brazil - Roxo, Fabio F. [UNESP]; Messias, Felipe L. [UNESP]; Silva, Gabriel S.C. [UNESP] (Magnolia Press, 2019)
A new species of Parotocinclus is described from the Rio Tocantins basin, Tocantins State, Brazil. The new species is distinguished from congeners by a combination of characters such as: (1) a unique pattern of body coloration with five transverse dark bars; (2) absence of an adipose fin or small platelet at typical adipose-fin region; (3) absence of conspicuous dark dots broadly distributed on the body; (4) absence of a triangular dark blotch at the anterior base of the dorsal fin; and (5) presence of a V-shaped spinelet.
Keywords: Cascudinhos; Freshwater; Neotropics; Siluriformes; Taxonomy